Peningkatan Kemampuan Pemecahan Masalahsiswa SMP Laksamana Martadinata Medan Melalui Pendekatan Matematika Realistik - Siswandi Siswandi (Jurnal MathEducation Nusantara, 2018)
Abstract This research is a quansi experiment research. The population of this research is the students of MP Laks. Martadinata Medan. The sample selection was done randomly by randomizing the class. Class VII students (1) as the experimental class were treated with realistic mathematics approach and the students of class VII (5) as control class treated by ordinary learning. Instruments used consisted of: problem solving test, emotional intelligence questionnaire, student activity, student answer process. Data analysis was done by t test and anava two lane. The main result of this research are: (1) Improvement of problem solving ability of mathematics obtaining realistic mathematics approach is higher than students using ordinary learning, (2) Improvement of emotional intelligence of students who get realistic mathematics approach is higher than students using ordinary learning, and (3) There is interaction between learning with students' initial ability to improve problem solving ability of mathematics Keywords: realistic mathematical learning, emotional intelligence